Agent-Based Modeling of Ethnic Mobilization: The Former Yugoslavia Case - Srbljinović, Armano (Array, 2002)
The term ethnic mobilization, as used in this paper, refers to the process of reviving latent ethnic identities. More specifically, we investigate what has already been described as social situations in which ethnic roles that used to have less social importance are, under certain circumstances, pushed up towards the highest-importance end of the scale, as it was the case in former Yugoslavia. We are more interested in exploring mechanisms by which this process happens than in exploring causes of such situations. In order to enable the explorations, we construct an agent-based model, combining and trying to improve some of the previously used representations of social networks and collective cognitive structures involved in the development of identity shaping and collective mobilization mechanisms. The agents are characterized by four basic variables: ethnic membership (blue or red) ; degree of ethnic mobilization - the degree to which an agent identifies with its ethnic group ; degree of "civic mobilization" - the degree to which an agent is committed to the values of civil society (increasing ethnic mobilization is assumed to decrease the civic one) ; and degree of grievance - the variable describing agent's satisfaction with its conditions of life: economic, political, security and others. In addition, each agent possesses its own "social network" representing the other agents with whom it communicates (family, friends, colleagues, etc.), and whose state variables it can observe. Such observations influence the state of agent's variables. During the simulation agents receive appeals. Appeals are characterized by their source (blue, red or grey - neutral), and content (increase/decrease mobilization level). Appeals are meant to represent various means - media, public meetings, etc. - by which particular subjects - state, political organizations, ethnic leaders, non-governmental organizations, etc. - influence individuals' ethnic/civic orientation. Agents react to received appeals by changing their state variables. By varying the initial conditions of particular model settings (i. e. agent constellations, appeal frequencies, types and targets), as well as the parameters of agents' perception and processing mechanisms, we are able to explore the influence of those factors on the efficiency of ethnic mobilization process. Preliminary results obtained by executing the model on selected portions of parameter space are presented. Complex model's behaviors obtained with relatively simple mechanisms, as well as the model's high sensitivity on random variations in the initial distribution of mobilization intensity and social networks may serve as indicators of inherent limitations on predictability of mobilization processes.